2022
DOI: 10.7241/ourd.20223.6
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo and quality of life: On fifty cases in Ouagadougou, Burkina Faso

Abstract: Background: Healthy skin with integrity is essential for maintaining one’s physical, mental, and social wellbeing. Vitiligo, a chronic autoimmune dermatosis characterized by asymptomatic, achromic macules, affects the integrity of the skin. Methodology: This was a descriptive, cross-sectional study conducted from March to June 2019 in six public hospitals in the city of Ouagadougou, Burkina Faso. The patients included in the study were followed in the dermatology departments of these structures for vitiligo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Spontaneous regression of the disease is slow, and distal body parts, such as the hands and feet, are more resistant to repigmentation than other body parts. The disease is associated with a decrease in patients' quality of life and may contribute to psychological disorders [2].…”
Section: Sirmentioning
confidence: 99%
“…Spontaneous regression of the disease is slow, and distal body parts, such as the hands and feet, are more resistant to repigmentation than other body parts. The disease is associated with a decrease in patients' quality of life and may contribute to psychological disorders [2].…”
Section: Sirmentioning
confidence: 99%
“…2,3 Several studies have shown that patients with vitiligo experience low self-esteem, body image issues, and social problems, which contribute to a lower quality of life. [4][5][6][7][8] Women, patients over 40, and people with darker skin tones may experience a greater impact on their quality of life. [9][10][11] People with vitiligo lesions in acral areas may have a lower quality of life due to the visibility of the lesion.…”
Section: Introductionmentioning
confidence: 99%